Impact of Sleep Deprivation on Academic Performance of Nursing Students at CMH, Lahore - Hira Tanveer, Ibtehaj Munir, Muhammad Osama, Muhammed Robass Zia, Irsa Rafique Chattha, Sehrish Zaffar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective was to establish a quantifiable link between sleep depression and GPA of nursing students. Study Design: This is a cross sectional, observational analytical study. Place and duration: It was conducted in CMH Lahore Institute of Nursing for a duration of 4 months. Methodology: A cross-sectional study was conducted at CMH Medical College, Lahore. A total of 41 willing students were included. After informed verbal consent, a predesigned questionnaire, adopted from similar studies, was used to obtain information regarding individual sleep hours, duty hours, perceptions regarding their sleep patterns and their GPA (academic performance). All the data was collected using Google Forms. The data was analysed using SPSS software. Results: A total of 41 participants were included in the study. The mean age of these participants was 19.76±0.97 years. Mean GPA was 3.44±0.21. Majority of the students believed that 12-hour shifts negatively impact their attention span in class (87.8 percent) and consequently their study routines (95.1 percent). A cumulative 82.9 percent of the participants felt that they needed more sleep for better patient safety and academic performance. Conclusion: The mean GPAs, sleep lengths, and wake/sleep times did not vary much within the sample population. However, apparent sleep quality and perceived tiredness varied significantly, with the respondents reporting a grave concern about patient welfare and future academic performance. Keywords: Sleep, sleep deprivation, GPA, performance.